2020
DOI: 10.1016/j.anbehav.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

How does individual variation in sociality influence fitness in prairie voles?

Abstract: Comparative studies aid in our understanding of specific conditions favoring the initial evolution of different types of social behaviors, yet there is much unexplained intraspecific variation in the expression of social behavior that comparative studies have not yet addressed. The proximate causes of this individual variation in social behavior within a species have been examined in some species but its fitness consequences have been less frequently investigated. In this study, we quantified the fitness conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Observations of 'adoptions' in kangaroos suggest that mother-young recognition may not be well developed [70]. Second, the time and cognitive effort needed by females with more differentiated social relationships to keep track of interactions with others could also reduce those mothers' time available for activities such as maintaining contact with young and anti-predator vigilance, as suggested by Montero et al [33] for yellow-bellied marmots and Sabol et al [71] for prairie voles (Microtus ochrogaster).…”
Section: Discussionmentioning
confidence: 99%
“…Observations of 'adoptions' in kangaroos suggest that mother-young recognition may not be well developed [70]. Second, the time and cognitive effort needed by females with more differentiated social relationships to keep track of interactions with others could also reduce those mothers' time available for activities such as maintaining contact with young and anti-predator vigilance, as suggested by Montero et al [33] for yellow-bellied marmots and Sabol et al [71] for prairie voles (Microtus ochrogaster).…”
Section: Discussionmentioning
confidence: 99%
“…However, we additionally repeated our main analyses removing 5% and 10% of weakest edges (see Supplementary Tables S1–S8 ). We chose these four metrics because previous studies showed that they influence mating in other systems (e.g., number of associates: Sabol et al 2020 , betweenness centrality: Oh and Badyaev 2010 , sex ratio: Grant and Grant 2019 ) and because we can make meaningful predictions of how they may influence mating outcomes in blue tits (see Introduction).…”
Section: Methodsmentioning
confidence: 99%
“…These studies show that not only the focal male’s phenotype but also the composition of the social environment (i.e., the other males’ phenotypes) influence its future success in acquiring a territory ( Farine and Sheldon 2015 ) or in gaining copulations ( Formica et al 2011 ; Wey et al 2015 ; Fisher et al 2016 ; Ziv et al 2016 ). Furthermore, it has been shown that more central or active individuals (in males: Formica et al 2012 ; Sih et al 2014 ; in females: Ziv et al 2016 ) and those with a higher number of social connections (both sexes: Sabol et al 2020 ) gain more copulations. However, many of these studies focused on nonmonogamous mating systems ( Formica et al 2011 , 2012 ; Sih et al 2014 ; Wey et al 2015 ; Ziv et al 2016 ) or examined mating success indirectly through the acquistion of nest sites ( Farine and Sheldon 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sociality, or the propensity of individuals to form social groups (Merriam-Webster., 2021), is a trait exhibited across taxa and varies between loose temporary aggregations to life-long associations (Alexander, 1974;Sabol et al, 2020). Social interactions have been shown to reduce predation risk and increase foraging efficiency, navigational capability, and reproductive opportunities Berdahl et al, 2018;Campbell et al, 2018;Diaz-Aguirre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%